Improving student learning enthusiast in the Geography Learning of Regional and Spatial concept through OIM techniques State High School 2 Bandar academic year 2019/2020 (Research, Society and Development, 2020)
This study aims to increase students' enthusiasm for learning in Geography Lessons on Regional Concept and Spatial Planning through OIM (Observe, Imitate, and Modify) Techniques in Class XII Social Science 2 State High School 2 Bandar Academic Year 2019/2020. This study uses a quantitative qualitative approach, mixed methods research design. The type of research used in this study is Classroom Action Research. In this study, the results showed that in the pre-cycle the score was 23.30, meaning that students' enthusiasm for learning was less. Then the first cycle produced an average score of 43.3 which means that students 'enthusiasm for learning is good, and then in the second cycle it produces an average score of 63.3 which means that students' enthusiasm for learning is very good. Based on the results, it can be concluded that in student observation activities, the teacher assesses that students can actively pay attention to the teacher's explanation in learning activities, students actively ask teachers or friends about material that has not been understood, students work on assignments given on time, students take advantage of the time there to discuss lessons, with friends and with teachers, students actively read books.